STUDI SUSUT UMUR TRANSFORMATOR DISTRIBUSI 20 kV AKIBAT PEMBEBANAN LEBIH DI PT.PLN (PERSERO) KOTA PONTIANAK - ., Parlindungan Gultom (Jurnal Teknik Elektro Universitas Tanjungpura, 2017)
AbstractDistribution transformer has a very crucial role on electrical power supply distribution system. In 1972, International Electrotechnical Commission (IEC) 354 claim if a transformer get a stable load on it’s identification power with ambient temperature 200C, transformer hot spot temperature will reach 980C and it’s lifetime became 20 years or 7300 days withnormal loss of life 0,0137% each day.Daily average ambient temperature in Pontianak is 300C, causing transformer’s load has to be adjust to avoid highloss of life.  Distribution transformer which installed on feeder Raya 10 has 11 units operating with daily load 80% - 100%of identification power and 8 units with over 100% daily load of identification power. Base on research that has been done we’ve come to conclusion that transformer which operating in Pontianak should not gain 91% load of identification power cause will decreasing the transformer lifetime drasticly. Keywords: distribution transformer, loss of life, ambient temperature, load.